(untitled) (Rajarshi Janak University Research Journal, 2025)
The manuscript explores how the Gen Z movement in Nepal has reshaped political culture and influenced the trajectory of democratic transition. Findings reveal that Gen Z activists, empowered by digital platforms, have challenged traditional party-centric politics and introduced a value-driven, transparency-oriented and issue-based political orientation. Their demand for accountability, ethical leadership and participatory governance has generated new expectations within the democratic process. While institutional rigidity, limited youth inclusion and digital divides remain significant challenges, the movement marks a critical turning point in Nepal’s evolving democratic landscape. This research methodology uses published secondary sources. Overall, Gen Z has emerged not merely as a protesting group but as a transformative force redefining Nepal’s democratic political culture.